Chapter The relation between students' educational performances and their access test results: a focus on an Italian case - Sechi, Agnese (Proceedings e report, 2023)
This paper aims at analyzing the relationship between university performances of freshman students, measured by the University credits (CUs) gathered during the first semester, and the results achieved in T.E.L.E.MA.CO. test, a useful tool for orientation and access to university studies based on solid scientific methodologies, and their social-demographic characteristics. This analysis is useful to understand when and how timely policies and programs can be implemented to avoid losing students, a frequent trend, especially in the first semester of the first year. All the considered students are enrolled at the Economic Department of the University of Genoa. Data provided directly by the Department are analyzed from a descriptive point of view and then a logit model is used to compute the probability of getting at least 15 CUs at the end of the first semester. Furthermore, the paper investigates the existence of a gender gap in mathematics before the beginning of university and after the first exams, based on the score gained in the admission test in the numeracy section (pre-university assessment) and the mark obtained in the mathematics exam (post-university assessment). Finally, this work attempt to explain if the university environment contributes to increase or reduce the gender gap.